Practice variation in the management of children hospitalized with bronchiolitis: A Canadian perspective. Issue 5 (3rd December 2018) - Jetty, Radha; Harrison, Mary-Ann; Momoli, Franco; Pound, Catherine
Abstract: Objectives: To describe variations in the monitoring, treatment, and discharge of children hospitalized with bronchiolitis among physicians across Canadian paediatric teaching hospitals. Methods: We conducted an electronic survey of paediatricians with experience in the management of inpatient bronchiolitis at 20 Canadian paediatric teaching hospitals. Only physicians who worked a minimum of 6 weeks on their hospital inpatient unit in the 2015 calendar year were eligible to participate in the study. The questionnaire explored the monitoring, treatment, and discharge of children with bronchiolitis. Central tendency (mean) and dispersion (SD) statistics were produced for continuous variables and frequency distributions for categorical variables. Results: A total of 142 respondents were included in the analysis. 45.1% reported the routine use of continuous oxygen saturation monitoring. 27.5% used a higher cut-off for oxygen supplementation of 92% and 12.7% use a lower cut-off of 88%. 29.6% routinely used deep nasal suctioning. Seventy-three per cent reported using nebulized therapies. 55.6% reported having preprinted order sheets or guidelines for management of inpatient bronchiolitis at their institutions and 28.2% reported having specific discharge criteria. The length of time required to be off oxygen prior to discharge varied (31% at 12 hours, 27.5% at 24 hours, and 24.6% after the last sleep period without oxygen). Conclusion: There is significant practice variation in the monitoring, treatment, and discharge of children hospitalized with bronchiolitis within and between Canadian paediatric teaching hospitals. Future research is needed to establish best practices, effective knowledge translation, and implementation strategies to standardize care and decrease length of stay.